Acute drug effects differentially predict desire to take dextroamphetamine again for work and recreation - Hoots, Jennifer K.; Webber, Heather E.; Nunez, Cecilia; Cooper, Jessica A.; Lopez-Gamundi, Paula; Lawlor, Victoria M.; Lane, Scott D.; Treadway, Michael T.; Wardle, Margaret C. (Psychopharmacology, 2021)
Rationale Misuse of dextroamphetamine occurs in work and recreational contexts. While acute drug effects broadly predict abuse liability, few studies have considered the relationship between acute effects and context. Objectives This study examined how individual differences in acute effects of dextroamphetamine relate to desire to take dextroamphetamine again in different contexts. Methods This secondary analysis used data from healthy adults with no history of moderate-to-severe substance use disorder, who received oral doses of placebo and dextroamphetamine (10 and 20 mg) over 3 sessions under double-blind, randomized conditions. Subjects rated subjective effects and completed reward-related behavioral tasks. Subjects rated their desire to take dextroamphetamine again in hypothetical work and recreational contexts. Multilevel models examined within-subjects change scores (10 mg-placebo; 20 mg-placebo) to determine how subjective effects and behavioral outcomes predicted desire to take dextroamphetamine again for work versus recreation. Results Subjects reported more desire to take 20 mg dextroamphetamine again for work than for recreation. At 20 mg, there was an interaction between context and liking/wanting, such that liking/wanting predicted desire to use dextroamphetamine for work only. There was also an interaction at 20 mg between context and psychomotor speed, such that psychomotor speed predicted interest in using dextroamphetamine for recreation only. Conclusions We found that positive subjective effects predicted desire to use dextroamphetamine again for work, while increased motor effects predicted desire to use dextroamphetamine recreationally. Hedonic effects may be perceived as advantageous when working, while increased physical energy may be preferred during recreation, suggesting that context of intended use is important when examining abuse liability.